Trajetórias sociais e vulnerabilidades associadas ao uso de crack e outras drogas: um estudo na cidade de São Paulo, Brasil (2023)
To address the needs of individuals dealing with issues related to the consumption of psychoactive substances within socially vulnerable settings, interventions are necessary. These interventions require comprehensive analysis of efficacy and effectiveness indicators, aiming to identify crucial aspects for the implementation of policies and programs focused on prevention, harm reduction, and treatment. Consequently, this study aimed to delineate the demographic profile of psychoactive substance users, examine their social trajectories, and identify vulnerabilities linked to the use of alcohol, crack, and other drugs in São Paulo's city center, specifically within the region commonly referred to as "Cracolândia". Employing a descriptiveexploratory approach, this mixed-methods study primarily utilized qualitative data obtained from a sample of 35 participants. The data underwent analysis through descriptive methodologies and content analysis. The findings revealed that this demographic faces a multitude of individual vulnerabilities as well as social and political-institutional challenges, such as educational and professional exclusion, detachment from familial and communal ties, homelessness, and limited access to social support services. Additionally, instances of violence and rights violations were observed, contributing to severe drug dependency. Notably, drug use was found to be a coping mechanism in response to adverse living conditions. It is hoped that these findings will inform comprehensive, integrative, compassionate, and ethically sound social and healthcare interventions, as well as public policies tailored to this specific population.